Pengaruh Konten Instagram Crosl.Store (Crsl.Store) terhadap Minat Beli - Dhiyyaul Hagi; Aminah Swarnawati (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2025)
In attracting consumers, every company has various strategies, including creating Instagram content with good ideas and visualisation to increase sales. One example of a fashion company that does this is crosl.store (crsl. store). Discovering the Instagram content at Crsl.Store, the buying interest of Crsl.Store consumers, and the extent to which Crsl.Store Instagram content influences buying interest are the main objectives of this study. According to this theory, Instagram posts (including Content Type, Stories, and Profile) and buying interest (including Attention, Interest, Desire, and Action) are the inputs. Using a descriptive survey method, this research takes a quantitative approach. In order to gather this information, we sent out surveys to all 77 people who followed the @crsl.store Instagram account. Methods of sampling based on the probability of occurrenceThat method of sampling is known as random sampling. From all statements of variable Y in the research questionnaire, it was found that the overall effect of Crsl.Store Instagram Content was well-received (agreed) by respondents. Additionally, respondents agreed with the overall effect of Instagram Content on Buying Interest. The magnitude of the influence of Crsl.Store Instagram Content was found to have a positive and strong relationship of 0.759 with the buying interest of Instagram followers @crsl.store as a percentage of Instagram Content.